Ayurveda and the Occupational Health (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda comprising advantageous, disadvantageous, happy and unhappy states of life along with wholesome, unwholesome aspects and it’s measurements, preached by Apta Purusha for Acharya searching for the extreme sources of Purusharth-Chatustaya the Longevity, foremost among three extreme desires of life. But there is no any grief greater than long life without proper resources, called second foremost desire, for which a person attends different occupations. But when desire comes to consumption or carried out without harmony creates several health disorders. i.e. why Shrotriya, Rajasevaka, Veshya and Panyajivina are considered as Extremely sick. It’s more intense today. Way of work, life style as well as several occupational hazards impart with Dosha, Dhatu, Mala, Shrotasa and other physiological and metabolic aspects of human body, which ultimately affect different systems of the body. However nobody intentionally does anything so as to invite mystery for himself. But those who are ignorant of the science of life sometime chooses wrong way for livelihood. So while attending their occupation a person needs to fallow certain measure. It includes Preventive, Promotive and Curative measures. If an action produces inauspicious results immediately or in long term then a wise person shouldn’t resort such type of work, because it has to be said that one should adopt only such means of livelihood as no clash with virtuous or wholesome path. Its violation has the power to destroy not only a person health rather whole of the environment which leads to Janpadodhwansa.